Semiotics of the Sensible: From Sensation to Intuition - Fontanille, Jacques (Semiotika, 2023)
Classifying semiotic systems by the sensory channels employed to communicate them is simple, but specious: we thus fail to inquire into that which is actually semiotic about different types of sensory experience. In order to explicate their distinctive semiotic properties, these sensory types – touch, hearing, vision, olfaction, sensomotorics – need to be interrogated as phenomena. This way, each of the semiotic sensible modes shall be characterized by a specific field of presence. Schematic forms of the sensible thus obtained will give rise to a typology of sensible “bodies” – the envelope-body, the cavity-body, the point-body, the flesh-body – as well as to a typology of their “dynamics” (deformation, intimate movements etc.) and, finally, to a typology of semiotic “imprints” which these dynamics give rise to. Next, we should interrogate the possibilities of employing such typologies in concrete analyses.Our primary presupposition is that, in most cases, objects of analysis – text, painting, film, choreography etc. – are multisensory, and thus the task of their explanation involves an articulation of several sensible modes. This kind of articulation is decisive for interpretation. The case of artworks is very suggestive in this sense: for example, in a painting, the same “visual” substances of expression can give rise to both a figurative and iconic presentation, grounded in the typical field of visuality, and to a plastic dimension which brings forth other types of field – somatic, affective, symbolic, or mythical.This means that the articulation of sensible modes is the object of a second-order schematization – the schematization of a trans-sensible dimension, wherein intuition produces schematic forms that become expressions for contents not directly determined by sensory modes. The trans-sensible dimension activates syntheses of sensible modes; as we have learned from Kant, these syntheses are not of the conceptual order: they are activated in intuition, make use of the imagination, and are always contained in the sensible order which is both sensory and emotional.
Keywords: sensation; sensible modes; field of presence; the trans-sensible; intuition